(untitled) (Historia, 2021)
A recent article in the South African Journal of Science (SAJS) has created a certain amount of anger in Afrikaner circles after Rapport newspaper published a piece on it. This was followed by a discussion by Professor Fransjohan Pretorius, in a critique entitled "Toiletpraatjies Stink". His comments bring to the fore some of the very real problems in writing a history of the camps.